To what extend does the type of ethical climate may predict missed nursing care in hospitals - Vryonides, Stavros; Merkouris, Anastasios; Charalambous, Andreas; Tsangari, Haritini; Papastavrou, Evridiki (My University, 2017)
To investigate and describe the types of ethical climate that may exist in the Public Hospitals ofthe republic of Cyprus, as they are perceived by Cypriot Nurses and the possible relationship that these types may have, with missed nursing care in these hospitals.
Keywords: Quality care; Working environment; Health care; Ethical Climate